Speaking Surfaces in James’s Siena - Gert Buelens (Viatica)
This essay examines anthropomorphised sites and buildings in “Siena Early and Late,” which convey a spectral quality that shines through apparently resistant surfaces. The challenge to penetration is welcomed more than deplored by James. He side-steps opportunities for in-depth probing, deriving profit from submission to an overpowering sense of historical significance and aesthetic meaning. That sense is sustained by the rhetorical power of the linguistic composition that takes place in James’s figurally excessive travel-writing.